The Added Value of Cerebral Imaging in Patients With Pyogenic Spinal Infection - Behmanesh, Bedjan; Gessler, Florian; Kessel, Johanna; Keil, Fee; Seifert, Volker; Bruder, Markus; Setzer, Matthias (Frontiers in Neurology, 2021)
Background The incidence of pyogenic spinal infection has increased in recent years. Beside treatment of the spinal infection early diagnosis and therapy of coexisting infections, especially of secondary brain infection, is important. Aim of this study is to elucidate the added value of routine cerebral imaging in the management of these patients. Methods Retrospective single center study. Cerebral imaging consisting of cerebral magnetic resonance imaging (cMRI) were performed to detect brain infection in patients with primary pyogenic spinal infection. Results We analyzed a cohort of 61 patients undergoing cerebral imaging after diagnosis of pyogenic spinal infection. Mean age in this cohort was 68.7 years and the gender distribution consisted of 42 males and 17 females. Spinal epidural abscess was proven in 32 (52.4 %) patients. Overall positive blood culture was obtained in 29 (47.5%) patients, infective endocarditis was detected in 23 (37.7%) patients and septic condition at admission was present in 12 (19.7%) Patients. Co-existing brain infection was detected in 2 (3.3%) patients. Both patients revealed clinical signs of severe sepsis, reduced level of consciousness (GCS score 3), were intubated and died due to multi organ failure. Conclusions Brain infection in patients with spinal infection is very rare. Additional brain imaging should be performed in patients with altered mental status and septic condition.